FEATURES OF ADMINISTRATIVE-TERRITORIAL REFORM OF POLAND - Бровко, О.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article deals with the administrative - territorial division of Poland to the reform of 1998. Analyzed administrative - territorial changes that took place in Poland as a result of the reform of 1998. The author examines the possibility of using the Polish experience to change the administrative - territorial structure of Ukraine.